Dependence of the hybrid solar cell efficiency on the thickness of ZnO nanoparticle optical spacer interlayer. (13th August 2017) - Vincent, Premkumar; Song, Dong-Seok; Jung, Ji-Hoon; Kwon, Jin-Hyuk; Kwon, Hyeok Bin; Kim, Do-Kyung; Choe, Eunji; Kim, Young-Rae; Kim, Hyeok; Bae, Jin-Hyuk
ABSTRACT: Optical spacer interlayers are commonly used in solar cells to improve the power conversion efficiency (PCE) of the device. This paper reports a study on the effect of zinc oxide (ZnO) optical spacer interlayer on PCPDTBT:ZnO hybrid solar cell. Optical spacers help to concentrate the spatial distribution of electric field due to light onto the active layer, and thus, improve the light absorption in the active layer. Finite-Difference Time-Domain (FDTD) calculations was carried out on stacked solar cell structure using a simulation software, Lumerical FDTD solutions. Maxwell's equations were solved and the light absorbed by the active layer was computed. The design was optimized with regard to active layer thickness and ZnO optical spacer thickness.